Discovery of potent IRAK-4 inhibitors as potential anti-inflammatory and anticancer agents using structure-based exploration of IRAK-4 pharmacophoric space coupled with QSAR analyses. (April 2019) - Khanfar, Mohammad A.; Alqtaishat, Saja
Graphical abstract: Highlights: IRAK-4 is a validated target for inflammation and oncology. Structure-based pharmacophore modelling combined with QSAR analysis was applied. Self-consistent and predictive QSAR model was identified. Several novel IRAK-4 inhibitors were discovered. Abstract: Interleukin-1 Receptor-Associated Kinase 4 (IRAK-4) has an important role in immunity, inflammation, and malignancy. The significant role of IRAK-4 makes it an interesting target for the discovery and development of potent small molecule inhibitors. In the current study, multiple linear regression -based QSAR analyses coupled with structure-based pharmacophoric exploration was applied to reveal the structural and physiochemical properties required for IRAK-4 inhibition. Manually built pharmacophoric models were initially validated with receiver operating characteristic curve, and best-ranked models were subsequently integrated in QSAR analysis along with other physiochemical descriptors. The pharmacophore model, selected using the statistically optimum QSAR equation, was implied as a 3D-search filter to mine the National Cancer Institute database for novel IRAK-4 inhibitors. Whereas the associated QSAR model prioritized the bioactivities of captured hits for in vitro evaluation. Experimental validation identified several potent IRAK-4 inhibitors of novel structural scaffolds. The most potent captured hit exhibited an IC50 value of 157 nM.